Overexpression of LiDXS and LiDXR From Lily (Lilium ‘Siberia’) Enhances the Terpenoid Content in Tobacco Flowers - Zhang, Tengxun; Sun, Ming; Guo, Yanhong; Shi, Xuejun; Yang, Yongjuan; Chen, Juntong; Zheng, Tangchun; Han, Yu; Bao, Fei; Ahmad, Sagheer (Frontiers in Plant Science, 2018)
Lilium, the famous and significant cut flower, emits a variety of volatile organic compounds, which mainly contain monoterpenes, such as myrcene, (E)-β-ocimene, and linalool. To understand the molecular mechanism of monoterpene synthesis in Lilium, we cloned two potential genes in the methylerythritol 4-phosphate (MEP) pathway, namely LiDXS and LiDXR, from the strong-flavored oriental Lilium ‘Siberia’ using a homology-based PCR strategy. The expression levels of LiDXS and LiDXR were consistent with the emission and accumulation of monoterpenes in different floral organs and during the floral development, indicating that these two genes play key roles in monoterpene synthesis. Subcellular localization demonstrated that LiDXS and LiDXR are expressed in the chloroplasts. Ectopic expression in transgenic tobacco suggested that the flowers of LiDXS and LiDXR transgenic lines accumulated substantially more diterpene, sclareol, compared to the plants transformed with empty vector. Surprisingly, increased content of the monoterpene, linalool and sesquiterpene, caryophyllene, were detected in the LiDXR transgenic lines, whereas the emission of caryophyllene, increased in one of the LiDXS transgenic tobacco lines, indicating that these two genes play significant roles in the synthesis of floral volatiles in the transgenic plants. These results demonstrate that LiDXR can contribute to monoterpene biosynthesis in Lilium ‘Siberia’; however, the role of LiDXS in the biosynthesis of monoterpenes needs further study.